2010
DOI: 10.1007/s00508-010-1470-6
|View full text |Cite
|
Sign up to set email alerts
|

Did you seek assistance for writing your advance directive? A qualitative study

Abstract: information about the medical implications concerning patient preferences for end-of-life care seems not to be the main focus of interest when individuals write an advance directive. Autonomy and trust into notarially certified documents seem to be more important matters. If family physicians want to have a role in their patients' completing of an advance directive, they should proactively get in touch with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…Besides the family, the physicians play an important role regarding ADs [14,15]. 22% of patients with ADs were supported by their family physician, and 4% by their specialist physician.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the family, the physicians play an important role regarding ADs [14,15]. 22% of patients with ADs were supported by their family physician, and 4% by their specialist physician.…”
Section: Discussionmentioning
confidence: 99%
“…5), whereas only few patients without completed ADs asked for legal consultation. This indicates that socioeconomic factors or personality traits such as safety needs might play a role in the patients' preferences for AD consultation [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Some cases, in which the patient’s family or proxy went to court to fight for these rights, showed that neither clinical practice nor decisions taken in local German courts were consistently in accordance with this judgment [3]. Therefore, the need for an explicit legal regulation on ADs became subject to a long public, political, judicial and medical debate, resulting in new legislation enacted in 2009.…”
Section: Introductionmentioning
confidence: 99%